A Critical Review on Efficient Thick‐Film Organic Solar Cells. Issue 11 (9th September 2020) - Gao, Jinhua; Wang, Jian; Xu, Chunyu; Hu, Zhenghao; Ma, Xiaoling; Zhang, Xiaoli; Niu, Lianbin; Zhang, Jian; Zhang, Fujun
Abstract : To date, the power conversion efficiency (PCE) of lab‐scale organic solar cells (OSCs) has exceeded 17%, which heralds the bright future for commercial applications of OSCs. High‐performance OSCs with thick active layers are essential for large‐scale production. First, the relatively thick active layers should be more compatible with the roll‐to‐roll (R2R) large‐area processing, which is conducive to forming uniform and defect‐free active layers in the process of high‐speed, mass production. Second, the thick active layers can absorb more incident light in their spectral range, which helps thick‐film OSCs to obtain relatively high short‐circuit current density ( J SC ). So far, relatively little attention has been paid to thick‐film OSCs, and the PCE of thick‐film OSCs lags far behind its thin‐film analogues. Herein, the recent development of thick‐film OSCs is highlighted and the critical limit factors on the PCE of thick‐film OSCs are pointed out. Some strategies are highlighted to improve the efficiency of thick‐film OSCs. This review study will be helpful to the researchers engaging in the development of efficient thick‐film OSCs. Abstract : High‐performance thick‐film OSCs are essential for well matching the roll‐to‐roll (R2R) technology to realize its large‐area potential application. The critical factors and smart strategies on performance improvement of thick‐film OSCs are well summarized to inspire more fantastic ideas on achieving efficient thick‐film OSCs. Meanwhile, the challenges on achieving efficient thick‐film OSCs are outlined.